Varve, paleomagnetic, and 14 C Chronologies for late Pleistocene events in New Hampshire and Vermont (U.S.A.) - Ridge, John; Bensonen, Mark; Brochu, Marc; Brown, Sarah; Callahan, Jamie; Cook, Glenn; Nicholson, Robert; Toll, Nathaniel (Géographie physique et Quaternaire, 1999)
Abstract A deglacial chronology for northern New England has been formulated using an atmospheric 14 C calibration of the New England Varve Chronology and paleomagnetic records. This 14 C chronology is based on 14 C ages from macrofossils of non-aquatic plants and is about 1 500 yr younger than existing chronologies that are based primarily on 14 C ages of bulk organic samples. The lower and upper Connecticut Valley varve sequences of Ernst Antevs (NE varves 2 701-6 352 and 6 601-8 500) overlap (lower 6 012 = upper 6 601) based on their crudely matching varve records and their similar paleomagnetic records. Three 14 C ages at Canoe Brook, Vermont (NE varve 6 150 = 12.3 14C ka) calibrate the lower Con necticut Valley sequence. New AMS and con ventional 14 C ages on woody twigs from Newbury, Vermont calibrate the upper se quence from 11.6-10.4 14 C ka (NE varves 7 440-8 660) and are consistent with the over lapping varve and paleomagnetic records, and the Canoe Brook 14 C ages. Deglaciation of the Connecticut Valley in southern Vermont began at 12.6 14 C ka (15.2 cal ka) and the Littleton-Bethlehem Readvance in northern New Hampshire and Vermont reached its maximum at11.9-11.8 14 C ka (14.0-13.9 cal ka) followed by recession of ice into Québec at about 11.5 14 C ka (13.4 cal ka). A lake persisted in the upper Connecticut Valley until at least 10.4 14 C ka (12.3 cal ka) and may have been seen by the first humans in the area.